Prevalence of fear of falling and associated factors among Japanese community-dwelling older adults. Issue 4 (January 2018) - Tomita, Yoshihito; Arima, Kazuhiko; Tsujimoto, Ritsu; Kawashiri, Shin-ya; Nishimura, Takayuki; Mizukami, Satoshi; Okabe, Takuhiro; Tanaka, Natsumi; Honda, Yuzo; Izutsu, Kazumi; Yamamoto, Naoko; Ohmachi, Izumi; et al.
Abstract : Abstract: To determine the prevalence of fear of falling and associated factors among Japanese community-dwelling older adults. Cross-sectional study between 2011 and 2013. Community in which residents voluntarily attended a health examination. We recruited 844 older adults (male, n = 350; female, n = 494) aged 60 to 92 years from among those who presented at the health examination. We assessed fear of falling, falls in the previous year, pain, comorbidity, and cataracts. Five times chair stand time was applied as an indicator of physical performance. The prevalence of fear of falling was 26.9% and 43.3% among the men and women, respectively. Men and women who feared falling were older ( P < .01), had longer 5 times chair stand time ( P < .01), and more falls in the previous year ( P < .05), pain ( P < .01), and comorbidity ( P < .05). Multivariate logistic regression analysis identified advanced age (odds ratios [OR], 1.57; 95% confidence interval [CI], 1.03–2.39), falls in the previous year (OR, 2.44; 95%CI, 1.29–4.64), and pain (OR, 1.82; 95%CI, 1.03–3.22) in men, and advanced age (OR, 1.59; 95%CI, 1.13–2.24), longer 5 times chair stand times (OR, 1.28; 95%CI, 1.04–1.59), falls in the previous year (OR, 2.59; 95%CI, 1.54–4.34), and pain (OR, 1.65; 95%CI, 1.06–2.55) in women as being independently associated with fear of falling. The prevalence of fear of falling was similar to previous reports. Advanced age, falls in previous year, and pain were associated with fear of falling in men. A longer 5 times chair stand time was also associated with fear of falling among older adult women. Maintenance of physical function and pain management might be important for older adults with fear of falling.